2017
DOI: 10.1038/srep46578
|View full text |Cite|
|
Sign up to set email alerts
|

Influenza C in Lancaster, UK, in the winter of 2014–2015

Abstract: Influenza C is not included in the annual seasonal influenza vaccine, and has historically been regarded as a minor respiratory pathogen. However, recent work has highlighted its potential role as a cause of pneumonia in infants. We performed nasopharyngeal or nasal swabbing and/or serum sampling (n = 148) in Lancaster, UK, over the winter of 2014–2015. Using enzyme-linked immunosorbent assay (ELISA), we obtain seropositivity of 77%. By contrast, only 2 individuals, both asymptomatic adults, were influenza C-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Seroprevalence studies for ICV have shown high rates, with the virus being distributed worldwide in the human population and initial exposure (infection) occurring during childhood ( 2 8 ), while recurrent infection with this virus occurs in both children and adults ( 9 ). Overall, as summarized in Atkinson et al ( 10 ), seropositivity has been reported to be between 57 and 100%, being lower in children and rising in adulthood. ICV has been considered a pathogen of low significance, as it generally causes mild disease or clinically inapparent infection ( 9 , 11 , 12 ), but in recent years it has become increasingly apparent that the virus can be associated with severe disease, notably in children with lower respiratory tract infections ( 12 18 ).…”
Section: Introductionmentioning
confidence: 96%
“…Seroprevalence studies for ICV have shown high rates, with the virus being distributed worldwide in the human population and initial exposure (infection) occurring during childhood ( 2 8 ), while recurrent infection with this virus occurs in both children and adults ( 9 ). Overall, as summarized in Atkinson et al ( 10 ), seropositivity has been reported to be between 57 and 100%, being lower in children and rising in adulthood. ICV has been considered a pathogen of low significance, as it generally causes mild disease or clinically inapparent infection ( 9 , 11 , 12 ), but in recent years it has become increasingly apparent that the virus can be associated with severe disease, notably in children with lower respiratory tract infections ( 12 18 ).…”
Section: Introductionmentioning
confidence: 96%
“…Deep sequencing was performed using an Illumina Nextera XT library and HiSeq 2500 system (SRA accession number SRP092324 ) ( 4 , 5 ). The variant sequences were assembled from the following sequence pools: pLUH01/Lancaster/2015/1 from 2 pediatric patients with respiratory symptoms (BioSample accession number SAMN05954284 ) and from 10 asymptomatic adults ( SAMN05954287 ); pLUH01/Lancaster/2015/2 from 6 chronic obstructive pulmonary disease (COPD) patients ( SAMN05954289 ); and pLUH01/Lancaster/2015/3 from a single asymptomatic adult ( SAMN05954290 ).…”
Section: Announcementmentioning
confidence: 99%
“…Our project (ref. 7 ) initially focussed on the prevalence and severity of influenza C infection in Lancaster, UK, during the winter of 2014–2015. We performed Ilumina deep sequencing on 9 patient pools (Data Citations 1–9), as detailed in Table 1 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Two of our 9 sequencing pools (Data Citations 8, 9) were from individuals diagnosed with influenza C infection via quantitative RT-PCR, from one of which we could partially assemble (ref. 7 ) the genome of a novel strain of influenza C, designated C/Lancaster/1/2015 (Data Citations 10–12). Within other sequencing pools we also detected the complete genomes of novel strains of human rhinovirus A22 (ref.…”
Section: Background and Summarymentioning
confidence: 99%